filmov
tv
Prove that sinA(1+tanA)+cosA(1+cotA)=secA+cosecA
Показать описание
Prove that sinA(1+tanA)+cosA(1+cotA)=secA+cosecA
Prove that sinA(1+tanA)+cosA(1+cotA)=secA+cosecA
Prove that sinA ( 1 + tanA ) + cosA ( 1 + cotA ) = secA + cosecA
Prove that sin theta(1+tan theta)+cos theta(1+cot theta)=sec theta+cosec theta | Trigonometry |
sinA(1+tanA)+cosA(1+cotA)=secA+cosecA
6. sinA(1+tanA)+cosA(1+cotA)=secA+cosecA Anuj Arjun classes
Find the solution of `sinA(1+tanA)+cosA(1+cotA)`
Prove that, sinA(1+ tanA) + cosA(1 + cotA)=secA + cosecA ! Easy Solution, BBA Hons, NU Business Math
Prove that : (1+cotA)/(cosA)+(1+tanA)/(sinA)=2(secA+cosecA) | 10 | MIXED PRACTICE | MATHS | IC...
Class 10 maths,Trigonometry, CHAPTER 8, NCERT SOLUTIONS, THE MATHS GURUDEV
cosec a - sin a sec a - cos a=1/tana+cota
Introduction to Trigonometry | Exercise: 4 | 5.(ix). (cosecA-sinA)(secA-cosA)=1/(tanA+cotA) |10 math
prove that√1+sinA/1-sinA=secA+tanA
|33.PT (cosecA-sinA)(secA-cosA)-1/tanA+cotA |in malayalam|
Prove that tana/1-cota+cota/1-tana=1+seca.coseca
Prove: (cosecA-sinA)(secA-cosA)= 1/(tanA+cotA)| Ex-8.4 Q5 (ix) | Class 10th Trigonometry
Prove that : cosA/1-tanA + sinA/1-cotA = sinA+cosA.
Prove that (CosecA-SinA)(SecA-CosA)=1÷(cotA+tanA) CBSE 2023
Prove that cosA/(1-tanA)+sinA/(1-cotA)=sinA+cosA
Prove that 1/(secA-tanA)= secA+tanA. 1/(secA-tanA)= secA+tanA.
Prove that : cosA/(1-tanA) + sinA/(1-cotA) = cosA+sinA ...|| Class 10 || rd question ||
prove (SinA/1-CosA)= (CosecA+CotA) | Class 10 NCERT Maths Trigonometry
#for √{(1+sinA)/(1-sinA)}=secA+tanA
Prove that: tanA/1-cotA + cotA/1-tanA = 1+secA.cosecA. | Class 10
Prove that sinA/secA + tanA - 1 + cosA/cosecA + cotA - 1 = 1
Комментарии